Pemanfaatan Lahan Pekarangan melalui Tanaman Pakcoy (Brassica Rapa Subsp. Chinensis) untuk Mendukung Ketahanan Pangan Keluarga - Defri Rahman; Ahmad Fachri; Juli Adevia; Muhammad Farrasky Delas Putra; Nova Suryani; Muhammad Satia Siregar; Oktia Verinda (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Community service aims to enhance family food security through the utilization of backyard land by cultivating pakcoy (Brassica Rapa Subsp. Chinensis). Pakcoy was chosen for its rapid growth, easy maintenance, and provision of nutritious harvest. The sustainable household food area approach was applied by involving families as the smallest unit in developing food security. The program includes education on farming techniques, crop diversification, and the economic benefits of utilizing backyard spaces. Through active community participation, the program successfully increased the availability of fresh vegetables for families, reduced dependence on external supplies, and stimulated local economic growth. In public service, they use the methods of lectures, discussions, questions and answers and practice. The results of the community service show that utilizing backyard land for pakcoy cultivation not only supports family food security but also yields positive impacts on economic and ecological aspects at the community level. The conclusions drawn from this community service provide a foundation for further development in efforts to achieve sustainable food security at the household level.